Elucidating the survival and response of carbapenem resistant Klebsiella pneumoniae after exposure to imipenem at sub-lethal concentrations. (3rd October 2018) - Low, Ye Mun; Chong, Chun Wie; Yap, Ivan Kok Seng; Chai, Lay Ching; Clarke, Stuart C.; Ponnampalavanar, Sasheela; Abdul Jabar, Kartini; Md Yusof, Mohd Yasim; Teh, Cindy Shuan Ju
ABSTRACT: The increasing prevalence of antibiotic resistant pathogens poses a serious threat to global health. However, less emphasis has been placed to co-relate the gene expression and metabolism of antibiotic resistant pathogens. This study aims to elucidate gene expression and variations in metabolism of multidrug resistant Klebsiella pneumoniae after exposure to antibiotics. Phenotypic responses of three genotypically distinct carbapenem resistant Klebsiella pneumoniae (CRKP) strains untreated and treated with sub-lethal concentrations of imipenem were investigated via phenotype microarrays (PM). The gene expression and metabolism of the strain harboring bla NDM-1 before and after exposure to sub-lethal concentration of imipenem were further investigated by RNA-sequencing (RNA-Seq) and 1 H NMR spectroscopy respectively. Most genes related to cell division, central carbon metabolism and nucleotide metabolism were downregulated after imipenem treatment. Similarly, 1 H NMR spectra obtained from treated CRKP showed decrease in levels of bacterial end products (acetate, pyruvate, succinate, formate) and metabolites involved in nucleotide metabolism (uracil, xanthine, hypoxanthine) but elevated levels of glycerophosphocholine. The presence of anserine was also observed for the treated CRKP while FAPγ-adenine and methyladenine were only present in untreated bacterial cells. As a conclusion, the studied CRKP strain exhibited decrease in central carbon metabolism, cell division and nucleotide metabolism after exposure to sub-lethal concentrations of imipenem. The understanding of the complex biological system of this multidrug resistant bacterium may help in the development of novel strategies and potential targets for the management of the infections.